Politiques de valorisation patrimoniale et figuration des habitants en banlieue parisienne (Plaine Commune) - Sébastien Jacquot (EchoGéo)
Plaine Commune, institutional territory from the Parisian suburbs, in Seine-Saint-Denis (french department), is characterized by heritage valorisation policies, particularly for tourism development. However the meaning of these policies has evolved. For a long time a classical type of heritage is valorized, as a testimony of national history. During the 1990s, a new conception of local heritage emerges and is promoted, that reflects the popular and industrial history of the territory. These heritage public policies have a symbolic dimension, producing discourses on the inhabitants, and defining their roles and places. These inhabitants are categorized in different ways by heritage public policies: as beneficiaries, witnesses, ambassadors, participants, and even tourists. These figurations also reveal a blurring of the distinction between inhabitant and institutions, redefining the logics of heritage public policies.